Analgesic Tolerance to High-Efficacy Agonists But Not to Morphine Is Diminished in Phosphorylation-Deficient S375A μ-Opioid Receptor Knock-In Mice - Grecksch, Gisela (J Neurosci, 2011)
Morphine is one of the most potent analgesic drugs. However, the utility of morphine in the management of chronic pain is limited by its rapid development of tolerance. Morphine exerts all of its pharmacological effects via the μ-opioid receptor. In many systems, tolerance is associated with phosphorylation and desensitization of G-protein-coupled receptors (GPCRs). In case of the μ-opioid receptor, phosphorylation occurs in an agonist-selective manner. High-efficacy agonists such as [d-Ala(2)-MePhe(4)-Gly-ol]enkephalin (DAMGO), fentanyl, or etonitazene stimulate the phosphorylation of both C-terminal threonine 370 (T370) and serine 375 (S375). In contrast, morphine promotes the phosphorylation of S375 but fails to stimulate T370 phosphorylation. Here, we have assessed the contribution of S375 phosphorylation to the development of antinociceptive tolerance to high- and low-efficacy μ agonists in vivo. We show that S375 phosphorylation of the μ-opioid receptor occurs in intact mouse brain in a dose-dependent manner after administration of morphine, fentanyl, or etonitazene. In knock-in mice expressing the phosphorylation-deficient S375A mutant of the μ-opioid receptor, morphine and fentanyl exhibited greater dose-dependent antinociceptive responses than in wild-type mice. However, acute and chronic tolerance to morphine was retained in S375A mutant mice. In contrast, antinociceptive tolerance after repeated subcutaneous application of etonitazene or repeated intracerebroventricular application of DAMGO was diminished. Thus, tolerance to μ agonists with different efficacies develops through distinct pathways. Whereas tolerance induced by DAMGO or etonitazene requires agonist-driven phosphorylation of S375, the development and maintenance of antinociceptive tolerance to morphine occurs independent of S375 phosphorylation.